ANALISIS KOMPARASI PRODUKTIFITAS USAHA TANI PADI SAWAH PADA MUSIM KEMARAU DAN MUSIM HUJAN DI DESA LAMONGAN KECAMATAN ARJASA KABUPATEN SITUBONDO PROVINSI JAWA TIMUR - Mayangsari, Andina; Fauzi, Farit Al (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Rice is an agricultural commodity that produces rice as the staple food of the Indonesian people, so various efforts have been made to achieve high productivity to meet the demand from the public for rice. However, for regions that have problems in the provision of irrigation water, special efforts must be made. So that efforts to increase the productivity of rice farming remain high. The reality is that in Situbondo Regency, East Java, irrigation water is regulated, with a rotating rice cropping pattern, some areas are planted during the dry season and some are planted during the rainy season. The aims of this research are: 1). To study the production of rice farming; 2). To analyze the difference in income; 3). To analyze the differences in the efficiency of rice farming in the dry season and rainy season in Lamongan Village, Arjasa District, Situbondo Regency. This research uses quantitative descriptive to prove the hypothesis that there are differences in production, income and efficiency (R/C ratio). Determination of the Research Area in Lamongan Village, Arjasa District, Situbondo Regency, East Java Province. The time of the study was July 2022 to August 2022. The results showed that the average dry season rice farming production was 9,125 kg, and the average rainy season rice farming production was 11,250 kg. The rainy season rice farming production was greater than production dry season. The average income of rice farming per dry season is IDR 1,732,727, and the average income of rice farming in the rainy season is IDR. 2,864,445; Rice farming income in the rainy season is greater than in the dry season. The average dry season rice farming efficiency is 1.74 greater than 1, while the rainy season rice farming efficiency averages 2.11 greater than 1. The rainy season rice farming efficiency is greater than the dry season efficiency.